(untitled) (International Current Pharmaceutical Journal, 2015)
The aim of study is to identify the antimicrobial property of ginger. Phytochemical screening of chloroform plant extract showed presence of different chemicals. In this study we used Cultures of E. Coli, Bacillus subtilis, Staphylococcus aureus and Streptococcus faecalis to identify the antimicrobial strength. Effectiveness of ginger against different conditions attributed to its different constituents (volatile oils, shogaols, Gingerols and diarylheptanoids) that show their therapeutic efficacy by modulating the genetic or metabolic activities of our body. In this study, we performed phytochemical evaluation and antimicrobial assay of ginger root extract which were available in our local farms of Lahore. Ginger possesses a noticeable antimicrobial activity which was confirmed by checking the susceptibility of different strains of bacteria and fungus by measuring the zone of inhibition. In the light of several socioeconomic factors of Pakistan mainly poverty and poor hygienic condition, present study encourages the use of spices as alternative or supplementary medicine to reduce the burden of high cost, side effects and progressively increasing drug resistance of pathogens. International Current Pharmaceutical Journal, June 2015, 4(7): 405-409